A novel approach towards sustainable banana farming intercropped with rubber by a smallholder - a profitable source of income diversification. - Kumara Thevan Krishnan; Suhaimi Othman; Amir Husni Mohd Shariff (2013)
In the year 2009-2010, the Department of Agriculture, Malaysia introduced Abandoned Land Development Project (ACDA). Under this project, abandoned lands are replanted with crops of economic value. The cultivator of this case study was one of the participants of ACDA project. With the subsidies provided by the goverment of Malaysia, the cultivator established a banana farm. Conventionally, the cultivator's main source of income should be generated from selling the banana fruit. However, we founds this cultivator cum entrepreneur diversified his land productivity. The monthly income generated from selling banan fruits, suckers and rubber seedlings were 30.2%, 39.9% and 29.9% of his total farm income, respectively. The cultivator provide a novel insight in managing banana farm by introducing new techniques of planting, fertilization regime and diversification of income in his banana farm intercropped with rubber seedlings